Prevalence of metabolic syndrome in a rural population- a cross sectional study from Western Uttar Pradesh, India - Zafar, Khwaja S.; Pious, Tony; Singh, Prem S.; Gautam, Rajesh K.; Yadav, Sudhir K.; Singh, Prafulla; Sharma, Himanshu (International Journal of Research in Medical Sciences, 2017)
Background: Prevalence of non-communicable diseases like hypertension, diabetes mellitus and coronary artery disease is on the rise due to the change in lifestyle, unfavourable dietary habits and obesity. Metabolic syndrome is a simple tool by which we can predict the future risk of diabetes mellitus and cardiovascular disease. Studies showed that prevalence of metabolic syndrome is rising in Indian population, but majority of them were done in urban population. This study was conducted to look into the current status of the metabolic syndrome in rural population. Methods: The study was conducted among a population of 2982. Each participant was subjected to clinical examination, anthropometric measurements and necessary laboratory investigations. Metabolic syndrome was diagnosed based on modified NCEP: ATP III criteria. Results: The prevalence of metabolic syndrome was found to be 11.7% and was higher among female population (13.8%) as compared to males (9.6%). The prevalence of metabolic syndrome increased with increasing age. 28.3% of the participants over the age of 50 years had metabolic syndrome whereas it was only 0.4% below the age of 20 years. Nearly half (47.1%) of the obese individuals were suffering from metabolic syndrome implicating obesity as one of the most important risk factors in the etiopathogenesis of metabolic syndrome. The prevalence was only 1.1% among the underweight group. Conclusions: Present study has shown moderate prevalence of metabolic syndrome among the rural population of Western Uttar Pradesh, India with a more female predisposition.